2023
DOI: 10.1051/mbcb/2023003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of buccal based triangular flap and lingual based triangular flap on postoperative course after impacted mandibular third molar surgery: a prospective randomized controlled study

Abstract: Introduction: The present study is to compare the buccal based triangular flap with lingual based triangular flap on postoperative pain, swelling and trismus after mandibular third molar surgery. Materials and methods: This study comprised of 100 patients, of which, 50 patients underwent buccal based triangular flap technique and 50 patients underwent lingual based triangular flap. The patients in both the groups were evaluated for pain, swelling and trismus on 1st, 3rd and 7th postoperative days. The wound he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, no previous study has directly compared these two interventions in terms of their efficacy on mouth opening, swelling, and pain. However, our findings are consistent with previous studies that have reported better wound healing and reduced postoperative complications with the use of modified flaps as compared to conventional envelop flaps 11,13 . It is important to note that further research with larger sample sizes and controlled confounding factors is warranted to validate these findings and provide more indepth understanding of the benefits of modified Newmann flap in postoperative recovery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, no previous study has directly compared these two interventions in terms of their efficacy on mouth opening, swelling, and pain. However, our findings are consistent with previous studies that have reported better wound healing and reduced postoperative complications with the use of modified flaps as compared to conventional envelop flaps 11,13 . It is important to note that further research with larger sample sizes and controlled confounding factors is warranted to validate these findings and provide more indepth understanding of the benefits of modified Newmann flap in postoperative recovery.…”
Section: Discussionsupporting
confidence: 93%
“…The main factor contributing to surgical trauma during third molar extraction is the lifting of a mucoperiosteal flap to properly see and reach the tooth. Various studies have been conducted to examine different flap designs as well as the impact of primary and secondary healing following the procedure 13,14 .…”
Section: Discussionmentioning
confidence: 99%